Behavioral Pattern Of Single Child And Child With Siblings: A Comparative Study - Roychan, Anoshka; Verma, Mamta; Podder, Lily (Pediatric Review: International Journal of Pediatric Research, 2025)
Introduction In this era of globalization, behavioral disturbances in young children are among the notable child health problems, the importance of which is increasingly recognized in most societies. About 8.9% children suffer from behavioral disorders worldwide and the most common age group for behavioral disorders is 6-11 years. This study intends to identify the domains most affected in a child brought up with siblings as compared to only child. Methods To assess the behavioral differences among single child and child with siblings, a comparative study was conducted in Bhopal, India with parents of 80 children in each group of 6-12 years’ age group (recruited by convenient sampling technique). The data was collected using Self- structured Child Behavioral Checklist containing eight domains, whose reliability was found to be r= 0.833. Result There was significant association in behavioral pattern of single child with sociodemographic variables like employment of parents and class in which the child studies whereas, variables such as parent’s age and birth order had significant association with behavioral pattern of child with sibling (p<0.05). Conclusion The study findings revealed that children without siblings were most affected with anxiousness during various situations of their life however,while considering children who were brought up with siblings had physiological problems as well as were more aggressive in nature. The current study provided the base for identifying the reasons for the domains being affected in both the groups. Keywords: Behavioral Pattern; Single child; only child; child with siblings; multiple children family; only child family